PTP1B inhibition promotes microglial phagocytosis in Alzheimer’s disease models by enhancing SYK signaling - Yuxin Cen; Steven R. Alves; Dongyan Song; Christy Felice; Jonathan B. Preall; Linda Van Aelst; Nicholas K. Tonks (Proceedings of the National Academy of Sciences, 2026)
Amyloid β (Aβ) accumulation is a hallmark of Alzheimer’s disease (AD). Emerging evidence suggests that impaired microglial Aβ phagocytosis is a key feature in AD, highlighting the therapeutic potential of enhancing this innate immune function. Here, we demonstrate that genetic deletion or pharmacological inhibition of protein tyrosine phosphatase 1B (PTP1B) ameliorated memory deficits and reduced Aβ burden in APP/PS1 mice. Moreover, we show that PTP1B was highly expressed in microglia, and its deficiency promoted a transcriptional shift toward immune activation and phagocytosis. Consistently, PTP1B deletion in microglia enhanced phagocytosis and energy metabolism, supported by increased AKT-mTOR signaling, a pathway essential for meeting the energy demands of activation. Mechanistically, we identified spleen tyrosine kinase (SYK), a key regulator of microglial phagocytosis, as a direct substrate of PTP1B. Inhibition of SYK showed that PTP1B modulates microglial activation in a SYK-dependent manner. These findings established PTP1B as a critical modulator of microglial activation and a potential therapeutic target for AD.